2018
DOI: 10.1093/jrr/rry062
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between pressure levels on the occipital region and intrafraction motion using an individualized head support for intracranial treatment

Abstract: The purpose of this study was to evaluate the relationship between pressure on the occipital region and intrafraction motion using an individualized vacuum pillow and a thermoplastic mask for intracranial treatment. We calculated head displacement during treatment from 8811 image verifications in 59 patients and divided them into two groups according to the magnitude of the mean and standard deviation (SD) of the displacement in the 59 patients. Pressure was compared between the small (n = 29) and large (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Inata et al showed that patient motion was reduced when the force on the occipital area was larger. 15 As shown in Figure 3 , the forces on the occipital bone at 1.5 h after the initial application were approximately 4 N in Plain and Folded methods. The force reached 80% of the maximum value in about 30 min in the Folded method, while it took about 1 h in the Plain and Wide methods.…”
Section: Discussionmentioning
confidence: 89%
“…Inata et al showed that patient motion was reduced when the force on the occipital area was larger. 15 As shown in Figure 3 , the forces on the occipital bone at 1.5 h after the initial application were approximately 4 N in Plain and Folded methods. The force reached 80% of the maximum value in about 30 min in the Folded method, while it took about 1 h in the Plain and Wide methods.…”
Section: Discussionmentioning
confidence: 89%
“…The measurement sensitivity of our monitoring system may have improved because the coefficient of displacement became smaller as the image interval became longer. We reported that the SD of the intrafraction displacement became small when an immobilizing pressure on the head was maintained at a high pressure level 20 . Hence, if a larger imaging interval is set, radiation exposure may be reduced with high positioning precision by means of maintaining a high pressure.…”
Section: Discussionmentioning
confidence: 99%
“…A baseplate (MT‐20108, CIVCO), a vacuum pillow (YCI‐01; Engineering System), and a mask (RT‐1779KS; Qfix) were used to immobilize the patients. The intrafraction displacement could be reduced by increasing the pressure in the occipital region to 15 kPa or more, as feasible 20 . Therefore, we inserted a foam sheet (made from natural rubber origin, with a thickness of 3 mm and a density of 0.100 ± 0.03 kg/m 3 ) under the pressure sensors to improve the sensitivity and equalization of pressure in the occipital region as compared to the procedure followed in our previous study 12 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations